Evaluation of Waste Water Treatment Units Located at Different Parts of Nepal - Lamichhane, Janardan; Upadhyaya, Bimal B; Chalise, Nishant; Makaju, Sudeep (Nepal Journal of Science and Technology, 2012)
Sewage including liquids from household waste to industry and commerce effluent along with storm water runoff carries various contaminants including soil particles, heavy metals, organic compounds, animals waste, oils and grease which are required to be treated before they are discharged directly to the water into waterways. Various waste water treatment plants established in different part of Nepal include small to large scale treatment of waste discharge. The evaluation of all those plants by scientific mean was carried out for the recommend of standard of treatment plant suitable to the country. Among the plants under study, removal efficiency of TSS, TDS and TS was found highest in KU reed bed systems with 97.5, 74.3 and 95.6% respectively. Similarly, removal efficiency of chemical compounds such as NH3, N2, NO3 2-, Cl-, PO3 2- and COD were found highest in KU and DH reed bed system ranging from 98 to 33.3 % whereas BOD was found highest, 93.1 and 82.1% in HIDWTP and BASP respectively. pH and conductivity measurement and comparison indicates the requirement of continuous use and maintenance of the plant. This could be one of the major ways to inform the government about the maintenance, sustainability and importance of ongoing operation of waste water treatment plants of Nepal in cost effective manner. DOI: http://dx.doi.org/10.3126/njst.v12i0.6500 Nepal Journal of Science and Technology 12 (2011) 201-210